Innovation in Developing Islamic Religious Education Curriculum at SDIT Insan Cermat - Aulia Geger Jagat EL-Zainie; Erihadiana; Hariman Surya Siregar (Yayasan Mentari Madani, 2023)
This research is to know and understand what the nature of the curriculum includes the understanding, role and function and innovation of the PAI curriculum at SDIT Insan Cermat, because the aim of educators in PAI subjects is not only a transfer of knowledge but an important thing from it is a transfer of value that will make students who are valuable and moral, have degrees because of their knowledge and have dignity because of their character. Using qualitative research methods. From the results of the presentation, conclusions can be drawn in: The progress of science and technology must be accompanied by moral progress in students. Innovations made in the PAI curriculum at SDIT Insan Cermat with a learning model that is able to answer problems in life that can be applied in the world of education are problem solving